Implementation of sustainable event on wedding activities at The Apurva Kempinski Bali - Fahrina Aprilla Hanani; Ni Nyoman Triyuni; Raden Ayu Trisnayoni (Unit Publikasi Ilmiah, P3M, Politeknik Negeri Bali, 2023)
This study aims to analyze the implementation of sustainable event management in weddings and its contribution to the environment, society, and the economy at The Apurva Kempinski Bali, Indonesia. The data collection method used in this study was by distributing questionnaires to 10 respondents and observing wedding event management. The data analysis method used is a descriptive statistical analysis by calculating the average and percentage of the questionnaire results. The results of the observations are described as reinforcement and explanation of the percentage results obtained from the questionnaire. The results of this study indicate that The Apurva Kempinski Bali has implemented sustainable wedding event management. The results of the questionnaire values obtained show a range of values from 2.60 to 3.40 which indicates poor implementation, then a range of 3.41-4.20 which states that it is implemented well, and a value range of 4.21 to 5.00 which states that it is implemented very well. Sustainable wedding events are currently being implemented in the hotel by establishing a sustainable wedding package program and several rules for implementing sustainability including permits and agreements. This implementation has had a positive impact on several indicators of sustainable activities at The Apurva Kempinski Bali.